2020
DOI: 10.5811/cpcem.2020.4.47557
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case Report of COVID-19 Presenting with Meningitis Symptoms and Shingles

Abstract: Introduction: As severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spreads across the globe, physicians face the challenges of a contagious pandemic including which patients to isolate, how to conserve personal protective equipment, and who to test. The current protocol at our hospital is to place anyone with new cough, dyspnea, or fever into airborne and contact precautions and consider them for testing. Unfortunately, the symptomatic presentations of coronavirus disease 2019 (COVID-19) are proving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 5 publications
(11 reference statements)
0
25
0
Order By: Relevance
“…Limb ataxia was reported in around 11% of the cases including the case reported by one of the authors of the present review. Other less reported neurological symptoms include tonic clonic seizures, slurred speech, [Panariello et al 2020, Yin et al 2020, McAbee et al 2020, Ye et al 2020, Duong et al 2020, Mukhergee et al 2020] Haemorrhagic-Frontal EDH [Al-olama et al 2020] Ischemic-Right caudate nucleus [Morassi et al 2020] Chronic microvascular change [Sohal and Mossamat 2020] 2 MRI NAD- [ref-Chaumont et al 2020, Karimi et al 2020, Dogan et al 2020, Bernard-Valnet et al 2020] T 2 [Wong et al 2020,Afshar et al 2020, Efe et al 2020 or T 2 /FLAIR hyperintensity- [ref-Efe et al 2020, Moriguchi et al 2020, Morassi et al 2020, Ramero-Sanchez et al 2020] Encephalitis like feature (hyperintensity, enhancement, haemorrhage) [Dogan et al 2020 (case nos 1, 2, 6)] DWI Restriction/ADC hypodensity [Moriguchi et al 2020, Hayashi et al 2020 Angiography CTA Beaded appearance- [Al-aloma et al 2020] MRA NA 5 MRS Choline peak- [Efe et al 2020] 4 Not available [Pilotto et al 2020, Packwood et al 2020, Chacon-Aguillar 2020, Talmor et al 2020, Romrero-Sanchez et al 2020, Varatharaj et al 2020 and cognitive difficulties such as verbal and motor perseveration. SARS-CoV-2 detection in CSF was reported in only 3 cases, whereas majority (92.6%) of the patients were diagnosed based on nasopharyngeal swab/oropharyngeal swab/bronchoalveolar lavage testing.…”
Section: Discussionmentioning
confidence: 99%
“…Limb ataxia was reported in around 11% of the cases including the case reported by one of the authors of the present review. Other less reported neurological symptoms include tonic clonic seizures, slurred speech, [Panariello et al 2020, Yin et al 2020, McAbee et al 2020, Ye et al 2020, Duong et al 2020, Mukhergee et al 2020] Haemorrhagic-Frontal EDH [Al-olama et al 2020] Ischemic-Right caudate nucleus [Morassi et al 2020] Chronic microvascular change [Sohal and Mossamat 2020] 2 MRI NAD- [ref-Chaumont et al 2020, Karimi et al 2020, Dogan et al 2020, Bernard-Valnet et al 2020] T 2 [Wong et al 2020,Afshar et al 2020, Efe et al 2020 or T 2 /FLAIR hyperintensity- [ref-Efe et al 2020, Moriguchi et al 2020, Morassi et al 2020, Ramero-Sanchez et al 2020] Encephalitis like feature (hyperintensity, enhancement, haemorrhage) [Dogan et al 2020 (case nos 1, 2, 6)] DWI Restriction/ADC hypodensity [Moriguchi et al 2020, Hayashi et al 2020 Angiography CTA Beaded appearance- [Al-aloma et al 2020] MRA NA 5 MRS Choline peak- [Efe et al 2020] 4 Not available [Pilotto et al 2020, Packwood et al 2020, Chacon-Aguillar 2020, Talmor et al 2020, Romrero-Sanchez et al 2020, Varatharaj et al 2020 and cognitive difficulties such as verbal and motor perseveration. SARS-CoV-2 detection in CSF was reported in only 3 cases, whereas majority (92.6%) of the patients were diagnosed based on nasopharyngeal swab/oropharyngeal swab/bronchoalveolar lavage testing.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was given ceftriaxone, acyclovir, amoxicillin, clarithromycin, and high-dose dexamethasone; however, the team decided to withdraw care after patient showed an extremely poor prognosis with no neurological improvement, and she died on the 10th day after admission. Encephalitis and meningitis were reported in SARS-CoV, MERS-CoV, and COVID-19 patients in nearly 39 cases [25,26,28,31,[41][42][43][44][45][46][47]. Arabi et al reported a case of a 45-year-old male with multiple comorbidities who presented with fever, respiratory symptoms, and diarrhea associated with MERS-CoV [25].…”
Section: Encephalopathy Encephalitis and Meningitismentioning
confidence: 99%
“…He complained of severe headaches and abdominal symptoms before the development of a rash. Typical chest symptoms and meningitis followed several days later [23].…”
Section: Clinical Features and Epidemiologymentioning
confidence: 99%